Development and characterization of flame retardant oil palm filler/kenaf reinforced hybrid composites - Saba, Naheed (2016)
Epoxy is among the most extensively used thermoset polymer in the composite industry, particularly for high performance and advanced applications. However, most cured epoxy systems are extremely brittle, poor resistance to crack initiation, possess lower impact strength and characteristics poor flame retardancy during fire threats, which limits its extensive applications. These weaknesses are more acute when used with natural fibers. To minimize these shortcomings flame retardant (FR) nano filler are incorporated as additive to improve its strength besides its flame retardancy. This study used oil palm empty fruit bunch (OPEFB) fibers obtained from palm oil processing mill for producing FR nano OPEFB. The FR nano sized OPEFB filler was produced through chemical (bromine water and tin chloride) treatment and cryogenic crushing followed by high energy ball milling process. Evaluation under SEM depicts that the surface morphology of the FR nano OPEFB possess amorphous and irregular shape. Thermal analysis revealed that the treated FR nano OPEFB is thermally stable compared to untreated OPEFB fibers. Residual char obtained is 29% for nano OPEFB, 10.85% for untreated (R-OPEFB) and 14.17% for B-OPEFB fibers. Epoxy nanocomposites were fabricated using different nano OPEFB filler loading (1, 3, 5 % by weight) through hand lay-up technique. A marked increase in mechanical properties and flame retardancy were observed for all filler filled epoxy nanocomposites, in particular at 3% loading. Tensile strength of 1% is 21.43MPa, 3% is 29.01 MPa and 5% is 22.61 MPa, while impact strength of 1% is 68.13% J/m, 3% is 98.71 J/m and 5% is 70.62 J/m are observed. LOI value for pure epoxy is 23%, 1% is 25 %, 3% is 29% and for 5% is 28% while, UL-94V ratings for pure epoxy is V-2, 1% is V-1, 3% and 5% is V-0. Mechanical in terms of tensile, impact and elongation at break, morphological, physical, structural, thermal in terms of decomposition temperature and char yield, dynamic mechanical in terms of storage modulus (E') and loss modulus (E"), Tg and damping factor, thermomechanical in terms of coefficient of thermal expansion (CTE) and flame retardancy analysis were conducted by fabricating kenaf/epoxy composites and kenaf/epoxy hybrid nanocomposites each at 40% by weight of kenaf fiber loading. Three types of hybrid nanocomposites namely, nano OPEFB/kenaf/epoxy, montmorillonite (MMT)/kenaf/epoxy and organically modified montmorillonite (OMMT)/kenaf/epoxy hybrid nanocomposites were fabricated. Considerable improvement in mechanical strength in terms of tensile, impact strength and elongation at break were realized by adding nano OPEFB filler in kenaf/epoxy composites. Tensile strength of kenaf/epoxy composites increases by 24.9% by adding nano OPEFB filler, while 56% increment was recorded by adding OMMT with respect to nano OPEFB/kenaf/epoxy hybrid nanocomposites. Impact strength of kenaf/epoxy increases considerably from 19.13J/m to 24.54 J/m by adding nano OPEFB filler, to 31.32 J/m by adding MMT and to 39.46 J/m by adding OMMT. The profound effects of the nano OPEFB filler addition in reducing void contents and number of fiber pull out from the fractured surface signifies the enhanced adhesion and interfacial bonding between kenaf fibers and matrix. Remarkable improvements in E', E" and Tg, while reduction in CTE as function of temperature by adding nano OPEFB filler were also noticed. Tg value for kenaf/epoxy was increased from 70.1 oC to 80.6 oC by adding nano OPEFB filler. LOI and UL-94V ratings of kenaf/epoxy are 24% and V-2 respectively but the addition of nano OPEFB filler to it increases to 30% and V-0 respectively, for MMT to 28% and V-1 whereas for OMMT to 30% and V-0 rating. Results of the analysis revealed that there are improvements in the properties of the nano OPEFB/kenaf/epoxy nanocomposites which are quite comparable with those of MMT/kenaf/epoxy nanocomposites but lesser than the OMMT/kenaf/epoxy hybrid nanocomposites, except for flame retardancy. In conclusion, the proposed method to develop FR nano OPEFB filler from waste OPEFB fibers represents simple and convenient way in terms of time and energy required for utilizing OPEFB fibers waste efficiently.